Role of good oral hygiene on clinical evolution of rheumatoid arthritis: a randomized study nested in the ESPOIR cohort. (3rd September 2019) - Mariette, Xavier; Perrodeau, Elodie; Verner, Christian; Struillou, Xavier; Picard, Nicolas; Schaeverbeke, Thierry; Constantin, Arnaud; Ravaud, Philippe; Bouchard, Philippe
Abstract: Objective: There is a relationship between RA and periodontal disease. We aimed to investigate if a good oral hygiene could improve activity of RA. Methods: The patients with RA according to ACR/EULAR 2010 criteria and included in the French early arthritis ESPOIR cohort were included in a randomized nested study into: (i) intervention group: general recommendations of good oral hygiene including teeth brushing, daily antiseptic mouthwash and twice a year scaling; and (ii) control group: no intervention. The primary end point was the delta DAS28-ESR. Results: Four hundred and seventy-two patients were randomized (238 in intervention and 234 in control). 92/238 from the intervention group accepted the procedure and 81 had a first visit to the dentist. 56% of patients had periodontal disease at baseline. Duration of RA was 9.0±0.7 years. Baseline DAS28-ESR was 2.7±1.3. After a median duration of 24 months, delta DAS28-ESR was −0.17±1.29 and −0.09±1.28 in intervention and control groups, respectively (mean difference (complier average causal effect): −0.37 (95% CI −1.12, 0.37), P = 0.33). In the intervention group, there was a significant decrease of the bacteria involved in the red complex: Porphyromonas gingivalis ( P = 0.002), Tannerella forsythia ( P = 0.002) and Treponema denticola ( P = 0.019). The patients with baseline periodontal disease and those who became negative for one red complex bacterium had a slightly more important decrease of DAS28-ESR. Conclusion: Oral hygiene instruction together with regular scaling and polishing of the teeth significantly decreased the load of periodontal pathogens but did not decrease RA activity. This intervention should be tested in patients with earlier RA and more active disease. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT01831648.